Steady-State and Dynamic Simulation Study of Reactive Distillation for FFA Esterification in Biodiesel Synthesis - Kusumaningtyas, Ratna Dewi; Prasetiawan, Haniif; Nugroho, Daniel Setiyo; Wulandari, Ajeng Riswanti; Istadi, Istadi; Hisyam, Anwaruddin (Jurnal Rekayasa Kimia & Lingkungan, 2021)
Reactive distillation (RD) holds promise for process intensification in biodiesel production since it integrates reaction and separation. It simplifies the process and enhances the conversion of the equilibrium limited reactions. To ensure the stability in RD operation, sensitivity study and process control simulation are necessary. In this work, RD was employed for free fatty acid (FFA) esterification of mixed non edible oils in biodiesel synthesis. Non edible oils used were waste cooking oil, crude jatropha oil, and crude nyamplung oil (Calophyllum inophyllum L). Simulation was conducted using ASPEN Plus V8.8. Sensitivity study was carried out to determine the effects of the operating condition alteration. A dynamic simulation was performed as a Proportional-Integral-Derivative (PID) controller tuning. It was revealed that the highest FFA conversion was 85%, achieved at the feed stage of 7, distillate rate of 0.22 kmol/hr, and oil to methanol molar ratio of 1:5. Level, pressure and temperature controls were installed in RD. Then, a dynamic simulation was applied as a PID controller tuning. Three different controller tuning methods, viz. Ziegler-Nichols, Cohen-Coon, and Internal Model Control, were studied. The best PID parameter was obtained by using Cohen-Coon method which provided fastest rise time, lowest settling time and lowest overshoot.